Tapioka Sebagai Bahan Penguat Kering Pada Proses Pembuatan Kertas Alkali - Triyanto Hadisoemarto; Nina Elyani (Balai Besar Kimia dan Kemasan, 1999)
The use of unmodified tapioca for dry strength additive in the wet end process of alkline handsheet paper forming, has been conducted. Although a bit lower in comparison with CMC, tapioca has a good strengthening effect on the sheet properties, i.e. tear, burst, tensile, and fold. The diifference is shown in water absorbency, the higher the use of CMC, the higher the increase in Cobb number, but it practically remains constant for tapioca. The optimum percentage of those two additives is considered to be 3 %.